THE IMPLEMENTATION OF THE EFFECTIVE STRATEGY FOR PRACTICING EXTEMPORANEOUS SPEECH STYLE IN PUBLIC SPEAKING - Yulanda, Novia (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2021)
This research deals with public speaking class, especially in extemporaneous speech. The purpose of the research was to find out how was the effective strategy for practicing an impromptu speech in public speaking. The researcher applied a qualitative research approach. The technique of data collection was note-taking by collected data on books and journals. The data were analyzed using data reduction, data display, and drawing the conclusion. The results revealed that there are some effective strategies for practicing extemporaneous speech in public speaking. The introduction of the speech started from greeting the god, getting the attention and interest of the audience started by a familiar quote, telling a personal story to illustrate speech point, and revealing the topic to the audience. Strategies explaining the body of speech were to have a card note. It is used to write the point of the speech presents the main points and sub-points in the body of the speech. Establish eye contact with the audience into speaker opening words, vocal and visual gestures in perform, and make sure the speech has the desired impact on the audience, testimony quotes from expert statements to support the conversation. Then, strategies concluding the speech began the conclusion with a restatement of the speaker's message by using positive words to the audience, praise and thanks to the audience, closing with an entertaining sentence or anecdote, chant rhymes, and chant rhymes and short poems.